Polymorphisms in TOX and NCOA2 genes and their associations with reproductive traits in cattle - Camargo, Gregorio M. F. de [UNESP]; Costa, Raphael B. [UNESP]; Albuquerque, Lucia G. de [UNESP]; Regitano, Luciana C. A.; Baldi, Fernando [UNESP]; Tonhati, Humberto [UNESP] (Csiro Publishing, 2015)
Reproductive traits are an important component of the economic selection index for beef cattle in the tropics. Phenotypic expression of these traits occurs late because they are measured when the animals reach reproductive age. Association studies using high-density markers have been conducted to identify genes that influence certain traits. The identification of causal mutations in these genes permits the inclusion of these single nucleotide polymorphisms (SNPs) in customised DNA chips to increase efficiency and validity. Therefore, the aim of the present study was to detect causal mutations in the TOX and NCOA2 genes, previously identified by genome-wide association studies of zebu cattle. DNA was extracted from 385 Nellore females and polymorphisms were investigated by polymerase chain reaction sequencing. Five polymorphisms were detected in the NCOA2 gene and four in the TOX gene that were associated with reproductive traits. Analysis of variance showed that SNP 1718 in the NCOA2 gene was significant for early pregnancy probability (P = 0.02) and age at first calving (P = 0.03), and SNP 2038 in the same gene was significant for days to calving (P = 0.03). Studies investigating polymorphisms in other regions of the gene and in other genes should be conducted to identify causal mutations.
Keywords: Molecular markers; Nellore; Sexual precocity; Single nucleotide polymorphism